Quantitative susceptibility mapping (QSM) and R2* of silent cerebral infarcts in sickle cell anemia - Murdoch, Russell; Stotesbury, Hanne; Kawadler, Jamie M.; Saunders, Dawn E.; Kirkham, Fenella J.; Shmueli, Karin (Frontiers in Neurology, 2022)
Silent cerebral infarction (SCI) is the most commonly reported radiological abnormality in patients with sickle cell anemia (SCA) and is associated with future clinical stroke risk. To date, there have been few histological and quantitative MRI studies of SCI and multiple radiological definitions exist. As a result, the tissue characteristics and composition of SCI remain elusive. The objective of this work was therefore to investigate the composition of segmented SCI lesions using quantitative MRI for R2* and quantitative magnetic susceptibility mapping (QSM). 211 SCI lesions were segmented from 32 participants with SCA and 6 controls. SCI were segmented according to two definitions (FLAIR+/–T1w-based threshold) using a semi-automated pipeline. Magnetic susceptibility (χ) and R2* maps were calculated from a multi-echo gradient echo sequence and mean SCI values were compared to an equivalent region of interest in normal appearing white matter (NAWM). SCI χ and R2* were investigated as a function of SCI definition, patient demographics, anatomical location, and cognition. Compared to NAWM, SCI were significantly less diamagnetic (χ = –0.0067 ppm vs. –0.0153 ppm, p < 0.001) and had significantly lower R2* (16.7 s−1 vs. 19.2 s−1, p < 0.001). SCI definition had a significant effect on the mean SCI χ and R2*, with lesions becoming significantly less diamagnetic and having significantly lower R2* after the application of a more stringent T1w-based threshold. SCI-NAWM R2* decrease was significantly greater in patients with SCA compared with controls (–2.84 s−1 vs. –0.64 s−1, p < 0.0001). No significant association was observed between mean SCI–NAWM χ or R2* differences and subject age, lesion anatomical location, or cognition. The increased χ and decreased R2* in SCI relative to NAWM observed in both patients and controls is indicative of lower myelin or increased water content within the segmented lesions. The significant SCI–NAWM R2* differences observed between SCI in patients with SCA and controls suggests there may be differences in tissue composition relative to NAWM in SCI in the two populations. Quantitative MRI techniques such as QSM and R2* mapping can be used to enhance our understanding of the pathophysiology and composition of SCI in patients with SCA as well as controls.